Optimizing methanol synthesis combining steelworks off-gases and renewable hydrogen. (January 2023) - Bampaou, M.; Haag, S.; Kyriakides, A.-S.; Panopoulos, K.D.; Seferlis, P.
Abstract: Renewable hydrogen improves the carbon balance of the methanol synthesis process but raises the production costs rendering a suitable hydrogen utilization strategy necessary. This work proposes different operating maps and reactor configurations that lead to improved hydrogen utilization and thus lower production costs. A mixture of steelworks off-gases is investigated as feedstock for the synthesis. At first, the conventional single-reactor loop operation is investigated, whereas in the second part, multi-reactor configurations are proposed to improve the process performance. Crucial operating variables are optimized to achieve optimum hydrogen utilization conditions for the investigated reactor setups. Results showed that recycling improved the performance in the single-reactor but no substantial improvements are observed for the multi-reactor setups. Overall, the four-reactor concept improves significantly the process efficiency that consequently could reduce the associated production costs: 13% lower hydrogen, 30% lower feedstock, 27% lower compression requirements and higher CO2 conversion (63%) per produced methanol unit. Highlights: Renewable hydrogen utilization is an important component in methanol synthesis. Multi-reactor setups and optimized conditions are investigated for improved hydrogen utilization. Recycling improves hydrogen utilization for conventional loop operation. The novel four-reactor concept results in overall better performance.